Microvascular obstruction in non-infarct related coronary arteries is an independent predictor of major adverse cardiovascular events in patients with ST segment-elevation myocardial infarction. (15th December 2018) - Khorramirouz, Reza; Corban, Michel T.; Yang, Shi-Wei; Lewis, Bradley R.; Bois, John; Foley, Thomas; Lerman, Lilach O.; Herrmann, Joerg; Oh, Jae K.; Lerman, Amir
Abstract: Background: Coronary microvascular obstruction (MVO) in infarct-related artery (IRA) territory has been associated with worse cardiovascular outcomes in patients presenting with ST-segment elevation myocardial infarction. However, the prognostic value of non-IRA MVO in this patient population remains unknown. Methods and results: One hundred ninety nine patients presenting to our institution with STEMI were enrolled. All patients underwent primary percutaneous coronary intervention per institutional STEMI protocol followed by a cardiac MRI within 1 week of presentation and the IRA and non-IRA MVO segments were determined. All cause death, recurrent myocardial infarction, hospitalization for heart failure, and ventricular tachycardia were counted as major adverse cardiovascular events (MACE). Patients with non-IRA MVO had lower composite MACE free survival at 6 months (HR 2.15, 95% CI, 1.06–4.35; p = 0.029) compared to those without non-IRA MVO. In a sub-analysis of patients with multi vessel disease (MVD), patients with non-IRA MVO also had lower composite MACE-free survival at 6 months as compared to those without non-IRA MVO (HR 2.47, 95% CI, 1.02–5.97; p = 0.037). Non-IRA MVO continued to be predictive of MACE in a cox proportional hazards model adjusting for additional prognostic factors using inverse probability weighting (p = 0.007). Non-IRA MVO was more prevalent in patients with LAD culprit vessel STEMI rather than those with RCA or Circumflex culprit vessels (p < 0.001). Conclusions: Patients presenting with STEMI and non-IRA MVO have significantly lower MACE free survival at 6 months as compared to those without non-IRA MVO. Highlights: Infarct-related artery (IRA) microvascular obstruction (MVO) is associated with major adverse cardiovascular events (MACE) Prognostic value of MRI-defined non-IRA MVO in patients with STEMI remains unknown Our study demonstrates that non-IRA MVO is an independent predictor of MACE (p = 0.007) in patients with STEMI Indeed, STEMI patients with non-IRA MVO have lower MACE free survival at 6 months (HR 2.15, 95% CI, 1.06 – 4.35, p = 0.029)